Impact of Piano Training on Physical, Cognitive Health, and Quality of Life of Older Adults at Changzhou Senior University Piano Teaching and Research Center: Intervention Program - Ge, Yier (International Journal of Social Sciences and Public Administration, 2026)
Piano training stimulates different cognitive functions, which is not only beneficial to brain plasticity and used by the elderly to compensate for age-related declines in executive function, but also beneficial to improving their quality of life in old age. This study analyzes the impact of piano training on the behavioral performance of the elderly through three indicators: processing speed, working memory, and cognitive flexibility. Through interviews, it also analyzes the promotion of piano training on the quality of life of the elderly and its impact on their physical function and cognitive health. The study finds that piano training can effectively improve the inhibitory control, working memory, and cognitive flexibility of the elderly, thereby promoting executive function plasticity and delaying age-related declines in executive function. At the same time, piano training can enrich the retirement life of the elderly and enhance their quality of life.